Kematian dalam Cerpen Superior Sidoarjo: Perspektif Psikologi Kematian - Hapriyanto, Lasmana Fajar; Ahmadi, Anas (UNIB Press, 2025)
Literary psychology, including the psychology of death, is rarely used as a theory in research. The rarity of research on the psychology of death in the context of literature makes this study unique and urgent. This study is expected to provide new insights into how death is perceived and explored in literary works, as well as how the psychological understanding of death. In life, death is an interesting issue. Anxiety about the coming of death, the cause of death, and narratives of death in literary works become an urgency that represents everyday life. This can be a reflection and learning in preparing for death. Therefore, this study aims to 1) examine the best short story literary works in Sidoarjo with the theory of literary psychology, focusing on the psychology of death, 2) examine more deeply the narrative of the type of death in short stories, 3) appreciate the best short stories in Sidoarjo. The method used is descriptive qualitative using reading and note-taking techniques. The data source is taken from the book Collection of Short Stories from the Best Young Writers Competition in Sidoarjo in 2021 with the title